Prenatal care satisfaction: perception of caregivers with diabetes mellitus - Bianca Fioravanti Nicolosi; Silvana Andréa Molina Lima; Meline Rossetto Kron Rodrigues; Carmen Maria Casquel Monti Juliani; Wilza Carla Spiri; Iracema de Mattos Paranhos Calderon; Marilza Vieira Cunha Rudge
ABSTRACT Objective: to understand the satisfaction of pregnant women with diabetes who took insulin during pregnancy and prenatal care performed through outpatient and inpatient follow-up. Method: a qualitative approach with analysis of 30 pregnant women who underwent prenatal care and participated in a clinical trial study carried out by the research group of the Perinatal Diabetes Research Center of the Hospital das Clínicas, of the Faculdade de Medicina de Botucatu. The data were collected through interviews and analyzed from content analysis. Results: from the category Satisfaction, the following subcategories emerged: facilities and difficulties faced in prenatal care performed through outpatient or inpatient follow-up, demonstrating that the pregnant women were satisfied with the prenatal care offered regardless of the type of follow-up. Conclusion: there was satisfaction in both care, but in outpatient care some structural, technical and administrative difficulties were identified, requiring reassessment, in order to guarantee service agility.